The Impact of Digital Marketing to Purchase Intention in Training Organizations - Setyowati, Devi; Sugiat, Maria Apsari (The Eastasouth Management and Business, 2025)
The growing penetration of the internet and advances in digital technology have significantly enhanced the marketing efforts of training organizations (LPKs) in Indonesia. Although many LPKs utilize digital marketing to support candidate placement in Japan, data from two institutions in East and West Java reveal that most trainees enrolled through channels other than social media. This study examines the impact of digital marketing on purchase intention in Indonesian LPKs. Using data collected from 384 respondents and analyzed with SEM-PLS 4.0, the results confirm a positive and significant relationship between digital marketing and purchase intention. These findings highlight the need for LPKs to develop stronger digital content strategies that resonate with their target audiences. The study is limited to two provinces and a quantitative method, which may not fully capture broader socio-cultural factors.